"Katerina gets mad": Infants' physiological and behavioral responses to co‐viewing educational, self‐regulatory media. Issue 8 (31st October 2022) - Porter, Chris L.; Stockdale, Laura A.; Reschke, Peter; Booth, McCall; Memmott‐Elison, Madison K.; Coyne, Sarah M.
Abstract: A growing body of research has focused on the physiological impact of media on older children and adolescents. Less research has been focused on the potential physiological impact of media on infants and younger children, especially media designed to be age appropriate and educational in content. In this study, we examined respiratory sinus arrhythmia (RSA) in infants ( N = 269, M age = 17.13 months) while they co‐viewed an educational video clip that modeled emotion regulation and contrasted their physiological response to an unoccupied baseline and a frustration paradigm (arm‐restraint). Given parent reports showing the calming effect of educational media viewing in young children, we anticipated that a similar pattern of calming would be observed physiologically in infants. Results showed that relative to baseline, most infants demonstrated an increase in RSA while co‐viewing, suggesting greater parasympathetic (regulatory) activation consistent with behavioral calming. However, infants who demonstrated vagal withdrawal during co‐viewing (decrease in RSA) were more likely to have parents who used a tablet to help infants go to sleep at night. Vagal withdrawal was also associated with increased levels of negative affect observed during the co‐viewing task. Findings are discussed in relation to the contextual effect of co‐viewing age‐appropriate, educational media on children's physiological responses.